NƯỚC CẤP ĐÔ THỊ Ở THỪA THIÊN HUẾ VÀ CÁC TÁC ĐỘNG TIÊU CỰC ĐẾN MÔI TRƯỜNG - Tuấn, Trần Anh (Nhà xuất bản Nông nghiệp, 2016)
Over the past several years, the use of urban water in Thua Thien Hue Province has dramatically augmented due to various reasons such as a rapidly increased number of users, recent prolonged droughts, expansion of provincial urban water supply networks, and so on. Prediction of urban water demand till 2020 conducted on the basis of per capita method in conjunction with extrapolation method shows that there will be a big challenge for HUEWACO to meet a double demand (320.000 m3/day) between now and 2020. The fact that the whole Thua Thien Hue Province will become a centrally-controlled city in the next several years makes the matter worse as the increasing urban water demand will bring about a lot of detrimental impacts on the province. For natural environment, an increased exploitation of water from Huong River might create lower flows that trigger river bank erosion and change of river bed topography, and reduce its environmental flow in summer causing negative impacts on the downstream ecosystems. The increased urban water usage also raise the amount of untreated wastewater from urban activities and sludge waste from the filtration processes of urban water plants. This exacerbates the pollution of nearby water bodies. As for socio-economic environment, a huge sum of approximately 543 billion VND, not including an extra amount for wastewater treatment, needs to be pumped in for meeting the demand in 2020. Thus, an in-depth study of such adverse impacts including clean water for the poor and the tapping of underground water is of great significance. It will definitely help to raise awareness on an efficient use of urban water for the sake of fresh water resources conservation and environmental protection.